Argeneau : Bad Luck Vampire - Book 36 - Sands, Lynsay (New York, NY : Avon, 2023)
"Alasdair MacKenzie has never once considered himself unlucky in all the centuries hes been an immortal rogue enforcer. Not until he meets Sophie. Finding the beautiful, smart, and funny woman who is his life mate is great luck, actually. But meeting her at a wedding full of Argeneaus, not to mention his own busybody uncles determined to "help him claim his woman," is bad luck. And the fact that Sophie is someone elses date? Well thats just the next level of unlucky. From the way her gaze travels over his body like a caress to the electric zing whenever they innocently touch...he has to have her! Hell keep his hands off Sophie until her date is over. After that all bets are off and hell pull out all the stops to win her for eternity. Great plan-until he gets hit by a car. And then hes poisoned. Is his luck that bad, or is someone out to stop this immortal from claiming Sophie as his life mate?"--
Keywords: Vampires -- Fiction; Vampire fiction; Romance fiction; Paranormal fiction; Novels